Immunomodulatory Effect of Polysaccharide Extracted from Sanghuangporus baumi Mycelia in LPS-Induced RAW264.7 Macrophages - Xiaoying MA; Jun XIAO; Na GONG; Guoli LIU; Xun CHEN; Tao YANG; Lan YAO; Changtian LI; Ying ZHAO (Shipin gongye ke-ji, 2023)
Sanghuangporus baumi is a kind of medicinal fungus with high activity. The aim of the present study was to investigate the immunoregulatory effects of Sanghuangporus baumi mycelia polysaccharides (SJ) on lipopolysaccharide (LPS)-induced RAW264.7 cells. In this study, Sanghuangporus baumi mycelia polysaccharides (SJ) were taken as the study subjects，and LPS-stimulated RAW264.7 macrophages were used as the cell model. The experiment was divided into three groups: Control group, LPS (model) and LPS+SJ groups. A CCK-8 kit was used to detect the viability of RAW264.7 cells. The effects of SJ on nitric oxide, and cytokines (IL-6, IL-1β, and TNF-α) production in LPS-stimulated RAW264.7 macrophages were measured by enzyme-linked immunoassay assay (ELISA). Furthermore, the effects of SJ on the protein levels of IL-6, TNF-α, IL-1β and inducible nitric oxide synthase (iNOS) were investigated by Western-Blot analysis. The results indicated that SJ increased 20.5%~50% cell viability at different concentrations compared to the control group. SJ at 200 μg/mL potently inhibited the release of nitric oxide and cytokine production in LPS-stimulated RAW264.7 (P<0.001), and compared with the LPS group, the secretion of NO, TNF-α, IL-6 and IL-1β decreased by 21.62%, 29.99%, 35.5% and 50.03%, respectively. Moreover, SJ also reduced LPS-induced protein expression levels of IL-6, TNF-α, IL-1β and iNOS in a dose-dependent fashion (P<0.001), and alleviated the inflammatory damage induced by LPS. And it was consistent with the change of cytokine secretion detected by ELISA method. The results of the present study suggest that Sanghuangporus baumi mycelia polysaccharides (SJ) have good immunomodulatory.